The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1556331620972629
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Telehealth in Total Joint Arthroplasty

Abstract: With the increase in technological advances over the years, telehealth services in orthopedic surgery have gained in popularity, yet adoption among surgeons has been slow. With the onset of the COVID-19 pandemic, however, orthopedic surgery practices nationwide have accelerated adaptation to telemedicine. Telehealth can be effectively applied to total joint arthroplasty, with the ability to perform preoperative consultations, postoperative follow-up, and telerehabilitation in a virtual, remote manner with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 47 publications
(94 reference statements)
0
20
0
Order By: Relevance
“…New technologies that have emerged, such as virtual goniometers, wearable sensors (wristbands) and app-based patient questionnaires, have improved clinicians’ abilities to conduct telehealth visits [ 38 ]. Digital technology platforms provide a scalable, meaningful approach to engaging patients throughout the continuum of joint replacement care and may serve as a cost-effective adjunct to traditional methods [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…New technologies that have emerged, such as virtual goniometers, wearable sensors (wristbands) and app-based patient questionnaires, have improved clinicians’ abilities to conduct telehealth visits [ 38 ]. Digital technology platforms provide a scalable, meaningful approach to engaging patients throughout the continuum of joint replacement care and may serve as a cost-effective adjunct to traditional methods [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some challenges still exist, including adaptation of new technologies and widespread accessibility, inability to conduct an in-person orthopedic physical examination and regulatory barriers, such as insurance reimbursement, increased medicolegal risk and privacy and confidentiality concerns. Despite these hurdles, telehealth is here to stay and can be successfully incorporated in any total joint arthroplasty practice with the appropriate adjustments [ 38 ]. There is sufficient evidence to recommend the use of telemedical methods in orthopedics [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of the fact that there is already some evidence for the acceptance and effectiveness of video-based and phone counseling formats (10,13,22,23,27), this exploratory study was able to show that especially in psychosomatic counseling, videotelephonic counseling can represent an essential and effective support function. As possible limitations, it should be noted that the present study was based on a single time point exploratory online survey in psychosomatic patients without follow up and without healthy control group.…”
Section: Discussionmentioning
confidence: 93%
“…It can be assumed here that in middle to increasing age, technical hurdles and complications could lead to feelings of being overwhelmed and to impairment of the consultation/therapy conversation. Prior research also suggested that with increasing age the tolerance level regarding technical hurdles or complications decreases and consequently the video contact cannot be fully utilized and may be perceived as unsatisfactory (27). However, despite potential difficulties and technical hurdles, regular use and greater support could reduce technical hurdles (3,28).…”
Section: Discussionmentioning
confidence: 99%
“…Within orthopaedic surgery, total joint arthroplasty (TJA) providers were early adopters of telehealth [ 5 , 6 , 7 ]. Although increased utilization of telehealth was evident in the first several months of the COVID-19 pandemic, it is not known if this represents a lasting or transient care delivery model in arthroplasty [ 7 ].…”
Section: Introductionmentioning
confidence: 99%